2000
DOI: 10.1007/pl00014093
|View full text |Cite
|
Sign up to set email alerts
|

Telematics: relevance for effectiveness of radiology

Abstract: IntroductionIf we look at the definition of telematics and its applications in radiology, we will find a wide range of contributing tools from computer hardware, software, network technique, and signal/image processing [1]. Since the present status and cost-effectiveness of PACS is presented in a separate contribution of the symposium, the current paper focuses on cost-effectiveness and benefit in patient care of teleradiology applications [2]. The presentation is divided into three parts:1. The first part dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Available studies showed a considerable reduction in potential transfer by the use of tele-medicine in neurosurgery: 37% potential transfer avoided in the study by Hassan et al (2014), 44% in the study by Moya et al (2010), 50% in the study by Heautot et al (1999), 64% in the study by Chodroff (1999) and 67% in the study by Kreutzer et al (2008). Similarly, some studies reported costs information: tele-radiology avoided 60% potential transfer costs in a study by Loose (2000), tele-medicine intervention reached breakeven point in a 15 months period with 282 neuro-surgical management (Kreutzer et al, 2008), a community tele-medicine intervention resulted in a net saving of $561,774 during 35 months period (Chodroff, 1999). A study from developing country also showed considerable savings with the help of tele-neurosurgery by reducing avoidable transfer (Hassan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Available studies showed a considerable reduction in potential transfer by the use of tele-medicine in neurosurgery: 37% potential transfer avoided in the study by Hassan et al (2014), 44% in the study by Moya et al (2010), 50% in the study by Heautot et al (1999), 64% in the study by Chodroff (1999) and 67% in the study by Kreutzer et al (2008). Similarly, some studies reported costs information: tele-radiology avoided 60% potential transfer costs in a study by Loose (2000), tele-medicine intervention reached breakeven point in a 15 months period with 282 neuro-surgical management (Kreutzer et al, 2008), a community tele-medicine intervention resulted in a net saving of $561,774 during 35 months period (Chodroff, 1999). A study from developing country also showed considerable savings with the help of tele-neurosurgery by reducing avoidable transfer (Hassan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%